Risk Management and Assessment - Rocha, Jorge; Oliveira, Sandra; Capinha, César (IntechOpen, 2020)
Risk analysis, risk evaluation and risk management are the three core areas in the process known as 'Risk Assessment'. Risk assessment corresponds to the joint effort of identifying and analysing potential future events, and evaluating the acceptability of risk based on the risk analysis, while considering influencing factors. In short, risk assessment analyses what can go wrong, how likely it is to happen and, if it happens, what are the potential consequences. Since risk is a multi-disciplinary domain, this book gathers contributions covering a wide spectrum of topics with regard to their theoretical background and field of application. The work is organized in the three core areas of risk assessment.